SALSA—A dance on a slippery floor with changing partners. (September 2017) - Reichhardt, M.P.; Holmskov, U.; Meri, S.
Highlights: Thesal ivarys cavenger anda gglutinin (SALSA) is the most abundant protein in human meconium and the infant intestine. SALSA binds to many microbes and endogenous ligands like IgA, lactoferrin, surfactant proteins and complement components. SALSA is a multifunctional molecule in innate immunity, inflammation and protection of mucosal epithelial layers. Different SALSA isoforms are found in chronic inflammatory conditions, such as Crohn's disease and ulcerative colitis. No SALSA has been detected in blood. Abstract: It is becoming increasingly clear that the connections between our immune system and the microbiota colonizing us have a tremendous impact on human health. A number of innate molecular defence mechanisms cooperate to selectively target unwanted microorganisms at the mucosal surfaces. Amongst others these include the complement system, IgA and the SALSA molecule. Thesal ivarys cavenger anda gglutinin (SALSA), also known as deleted in malignant brain tumors 1 (DMBT1), salivary agglutinin (SAG) or gp340 is a multifunctional molecule with important functions in innate immunity, inflammation and epithelial homeostasis. The SALSA protein is expressed at most mucosal surfaces, where it is one of the most abundant proteins. In the fetal meconium and infant intestine it may constitute even up to 10% of the total protein amount. SALSA is found either directly associated with the epithelial surface or secreted into the lining fluids. In the fluid-phase SALSA interacts with a number of bacterial and viral organisms, as well as with endogenous ligands, including IgA, lactoferrin, surfactant proteins and complement components. While complement has been shown to impact the mucosal environment, this remains an area of limited research. The multiple interactions of the SALSA molecule provide a scaffold, where this potent defence system may engage in cooperative microbial clearance together with corresponding mucosal host ligands. With its high abundance, and multiple effects on both host and microbes, the SALSA molecule is a key player in maintaining the immunological balance at the mucosal surfaces. This is further supported by observations linking the expression of different SALSA isoforms to the development of chronic inflammatory conditions, such as Crohn's disease and ulcerative colitis. This review describes the latest advances in understanding functions of SALSA and its different isoforms. Recently recognized functions are related to complement activation and regulation, endothelial development and epithelial homeostasis. In addition, we suggest mechanisms how SALSA regulates inflammation at the mucosal surfaces.